A study of design Mix concrete properties by using natural additives - Mahesh, M; Durga Naga Laxmi Devi, D (International Journal of Engineering and Technology, 2018)
Originally, Concrete mix contains cement, sand and coarse aggregate is a general proportion. But it contains short falls of properties which affects the strength of concrete which is used for construction.Now-a-days the technology is enhanced to overcome the short falls and to improve the strength of concrete by using natural & artificial additives like organic & inorganic.The present study on plain concrete by using organic additives like coconut fiber & bagasse is mixed with cement, sand & coarse aggregate in terms of different percentages of additives to impact the strength of concrete ability.The additives like coconut fiber is mixed in proportion in terms of percentage 0.5, 1.0, 1.5 and bagasse percentage is also taken as 0.5, 1.0, and 1.5 to find out the compressive strength of concrete. Total Number of Cubes for both additives of each percentage tested 9 Cubes as per IS 456:2000 to find out the Characteristic strength of Plain concrete for 7days, 21 days and 28 days.The aim of this study is to check the concrete strength compared separately for both natural additives like bagasse & Coconut fiber. Â Â